A qualitative investigation on career barriers and career preparation behaviors of third culture kids in south Korean colleges - Shin, Kahyen; Ra, Young-An (Frontiers in Psychology, 2024)
The purpose of this study is to explore career experiences of South Korean Third Culture Kids (TCKs) and to examine their career barriers and career preparation behaviors. For these aims, eight South Korean TCKs were interviewed and Consensual Qualitative Research (CQR) was used to analize the interview data. As results, two domains, career barriers and career preparation behaviors were developed. For career barriers and career preparation behaviors of TCKs, five each core ideas were reported. At the end of the study, we offered discussions and implications for higher education professionals and career counselors. The findings of the present study will contribute to the career development of TCK populations.